The Machiavellian Dimension of Auditors: An Exploration of Ethical Dilemmas in Auditing - Lidya Aprillia; Dewi Darmastuti (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2024)
Intense competition in the field of auditing necessitates the enhancement of auditors' skills and professional qualities, given their critical role in financial oversight and fraud prevention. This study examines the Machiavellian traits among auditors by conducting in-depth interviews with three informants from the Big Four public accounting firms. Employing a qualitative phenomenological approach, the research aims to delve into the complex nature of auditors' behaviors and ethics. The study utilizes source triangulation to validate the data, involving interviews with three seasoned auditors. The findings indicate that maintaining client relationships is deemed highly significant within the external auditing profession. Moreover, the research highlights that external auditors must embody independence and integrity, steering clear of manipulative and deceptive practices. The implications of this study stress that both junior and senior external auditors are required to adhere strictly to established professional standards and ethical codes. This adherence is crucial to mitigate the influence of Machiavellian tendencies that could compromise the integrity of audit outcomes.